Modulatory effects of White Tea (Camellia sinensis L.) on genotoxicity in Streptozotocin and Cyclophosphamide-treated Drosophila melanogaster’: Modulatory effects of White Tea on genotoxicity - FİDAN, Mehmet and AYAR, Arif (Progress in Nutrition, 2021)
In the present study, it was aimed to determine the antigenotoxic activity of white tea against the genotoxic effect caused by two different alkylating antineoplastic cancer drugs streptozotocin (STZ) and cyclophosphamide (CP) in Drosophila melanogaster through the somatic mutation and recombination test (SMART). During the application of SMART, two different mutant strains were used in the genome of D. melanogaster, with the determinant genes being recessive flare (flr3) and multiple wing hairs (mwh), respectively. Trans-heterozygous larvae of 72±hours, obtained through the crossbreeding of these two mutant strains, were chronically fed with white tea extract of different concentrations (0.625, 1.25, 2.50, and 5 mg/mL). In our study, the LD50 values of the relevant drugs were also found (STZ: 0.25 mg/mL, CP: 2.5 mg/mL), and it was determined that both drugs have a fairly high genotoxic effect (p<0.05). Afterward, white tea extracts of different concentrations were applied to larvae simultaneously with cancer drugs. From the data obtained, it was determined that white tea extract significantly reduced the clone induction frequency (CIF) in all treatment groups, by suppressing mutations enabling the formation of spots in wings, in parallel with the increasing concentration. Furthermore, when the inhibition percentage rates were subjected to examination in order to determine white tea’s reduction rate of the genotoxic effect caused by cancer drugs, it was determined that the relevant rate was 55.79% in the 0.25 STZ+2.5 White Tea treatment group, and 60.00% in the 2.5 CP+5 White Tea treatment group. In conclusion, it was concluded that streptozotocin and cyclophosphamide drugs used in cancer treatments might create genotoxic effects even in healthy cells, and these effects might be reduced by additional white tea consumption